Lessons Learned by the Strong Local Earthquake at the Petrochemical Plant - Y. Wada; M. Wakakura; Y. Hayashi; N. Takagi; H. Oba; M. Kumasaki; A. Miyake; M. Arai (Chemical Engineering Transactions, 2013)
On 11 and 12 April, 2011, unexpected strong local earthquakes stroke petrochemical plants in Fukushima Prefecture. That local earthquake is caused by the old active fault near the plant activated by the Great East Japan Earthquake. The plants were attacked by the Great East Japan Earthquake, and all facilities of the plant had been stopped since 11 March, 2011. In spite of having received twice earthquakes (especially the bigger second local earthquake), damages of main facilities of the plant were little. The investigation team constituted by specialists of material safety, plant engineering and engineers of that petrochemical company, searched the damage of the facilities and emergency response, and recovery efforts. We summarized the lessons learned from the large earthquake of the chemical plant, related with the emergency correspondence and its organization, support for surrounding, recovery and reconstruction program, etc.